(untitled) (Research, Society and Development, 2021)
In Brazil, it is possible to massively identify scenarios full of social gaps and plagued by inequality. In this way, public policies are presented as central instruments to settle disparities within society. Such initiatives are developed by the State, through the principle of the common good, and from the interrelation with social institutions such as Universities, centers of intellectual production, there is the optimization of the results of these social endeavors. This article aims to identify the benefits and impacts of university extension in the face of social inequalities. To this end, we sought to present, through bibliographic research, the structure of the Tutorial Education Program and the analysis of its contribution as a public policy based on the performance of the PET Integração group at the Federal University of Piauí. It was concluded that the extension actions were effective in mitigating social discrepancies, figuring as suitable tools for public policy.